(untitled) (Research, Society and Development, 2023)
In order to obtain a quality endodontic treatment, it is necessary to have a detailed knowledge of the internal and external anatomy and its possible variations. The ’C’- shaped canals are anatomical variations characterized by having the canals in the form of a ribbon or arc, which can be united, single or separate. These have a complex anatomy, which requires adequate planning and execution of each operative step, including the diagnosis, in order to achieve a satisfactory result. The prevalence of this type of variation involves regional aspects and also the patient’s gender and ethnicity, affecting more upper and lower first and second molars. Knowledge about them and a thorough exploration of diagnostic radiography is essential for planning and executing the treatment. The objective is to report a clinical case of a 41-year-old female patient, where the diagnosis and management of a molar lower tooth, tooth 47, with anatomical variation in ’C’, where instrumentation was performed using the hydroid technique (mechanized with reciprocating movement with complementation of oscillatory instrumentation), medication with calcium hydroxide and obturation using Tagger’s Hybrid Technique. The case was performed in the clinic of the specialization course in Endodontics at AMO - Associação Maringaense de Odontologia, Maringá-PR.